Effects of legume consumption on serum cholesterol, biliary lipids, and sterol metabolism in humans - Duane, W.C. (Veterans Affairs Medical Center, Minneapolis, MN.) (Journal of lipid research, 1997)
Legume consumption appears to lower serum cholesterol and to increase cholesterol saturation of bile, but the mechanisms of these effects have not been established. We studied nine human subjects on a metabolic ward during two randomly ordered 6-7 week periods: one during consumption of a control diet and the other during consumption of the same diet with 120 gm mixed legumes substituted for foods having equivalent calories, fat, protein, and carbohydrate. Mean serum LDL cholesterol was significantly lower during legume consumption (126 vs. 138 mg/dl, P = 0.039). Legume consumption significantly increased mean cholesterol saturation index of gallbladder bile from 1.07 to 1.26 (P = 0.016), largely because of an increase in hepatic secretion of cholesterol from a mean of 90.2 micromole/h to 100.8 micromole/ h (P = 0.042). Fecal neutral sterol output was unaffected by legumes, but fecal acidic sterols increased from a mean of 861 to 1202 micromole/day (P = 0.002) during legume consumption. Mean sterol balance became significantly more negative during legume consumption (-2140 vs. -2700 micromole/day, P = 0.037) indicating an increase in cholesterol synthesis. Mean fractional absorption of bile acid was lower during legume consumption than (0.947 vs. 0.960, P = 0.003). These data suggest that legume consumption lowers LDL cholesterol by partially interrupting the enterohepatic circulation of bile acids and increases cholesterol saturation of bile by increasing hepatic secretion of cholesterol